The Effectiveness of Massage Therapy in Reducing Fatigue among Cancer Patients Undergoing Chemotherapy: Systematic Review - Ahmad Fadhlur Rahman; Dewi Gayatri; Giur Hargiana (GLOBAL HEALTH SCIENCE GROUP, 2025)
Fatigue is one of the most common side effects experienced by cancer patients undergoing chemotherapy and has a serious impact on quality of life. Massage therapy has emerged as a potential non-pharmacological intervention to alleviate this symptom. Objective: To systematically review the effectiveness of massage therapy in reducing fatigue among cancer patients undergoing chemotherapy. Methods: This study employed a systematic review design based on the PRISMA guidelines. Literature was searched through PubMed, ScienceDirect, ProQuest, and Google Scholar databases. Articles published in English or Indonesian in the last 10 years (2014–2024). Included articles were randomized controlled trials (RCTs), quasi-experimental studies, or clinical trials evaluating the effects of massage therapy on fatigue in cancer patients. 139 Articles were founds and 10 article were selected. Study quality was assessed using the CASP tool, and data were analyzed descriptively. Results: A total of 10 studies met the inclusion criteria. Findings showed that massage therapy—including slow-stroke back massage, Swedish massage, hand and foot massage, and combinations with aromatherapy—was effective in reducing fatigue. The effectiveness was influenced by the type of massage, duration, and frequency of the intervention. Conclusion: Massage therapy is an effective intervention that can be integrated into clinical care to reduce fatigue in chemotherapy patients. Further research is needed to strengthen the existing evidence.